Alg

posted by K- ASAP!!!!

Given f(x) = 2x^2 – 2 and g(x) = –2x + 4, find the following.
(f − g)(2)

AND
Given f(x) = 2x − 2 and g(x) = 4x − 5, evaluate the composite function.
f[g(2)]

  1. Steve

    (f-g)(2) = f(2) - g(2)
    = 2*2^2-2 - (-2*2+4)
    = 6 - 0
    = 6

    f(g(2) = 2*g(2) - 2
    = 2(4*2-5)-2
    = 2*3-2
    = 4

Respond to this Question

First Name

Your Answer

Similar Questions

  1. Math

    First, give the technology formula for the given function and then use technology to evaluate the function for the given values of x. (Round your answers to four decimal places.) r(x) = 4x2 + 1/4x2 − 1; x = −1, 0, 1, ..., …
  2. Math: Pre Cal

    f(x) = {−8 if −3 ≤ x ≤ 0 {x if 0 < x ≤ 3 Evaluate the given expressions. a)f(-1)= b)f(0)= (^Teach how to do this.) What is the formula?
  3. biology

    Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
  4. Grade 12 Calculus

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  5. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  6. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  7. Algebra

    Given f(x) = 2x − 1 and g(x) = 4x − 4, evaluate the composite function. g[f(x)]
  8. Calculus

    Find the first partial derivatives and evaluate each at the given point. Function w = 2x^2y − 6xyz + 10yz^2 Point (2, 5, −3) wx(2, 5, −3) = wy(2, 5, −3) = wz(2, 5, −3) =
  9. Calculus

    Find the first partial derivatives and evaluate each at the given point. Function w = sqrt(5x^2 + y^2 − 4z^2) Point (2, −4, 2) wx(2, −4, 2) = wy(2, −4, 2) = wz(2, −4, 2) =
  10. Algebra 1

    Evaluate the following expression using the values given: Find 3x^2 − y^3 − y^3 − z if x = 3, y = −2, and z = −5. Numerical Answers Expected! thanks so much if you could help me. This is for an exam and …

More Similar Questions